2017
DOI: 10.1002/bjs.10302
|View full text |Cite
|
Sign up to set email alerts
|

Potential value of routine contralateral patent processus vaginalis repair in children with unilateral inguinal hernia

Abstract: Laparoscopic inguinal hernia repair was associated with a lower recurrence rate than open repair. Routine repair of CPPV reduced the rate of subsequent MIH, but 21 CPPVs needed to be closed to prevent one MIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…[15] A study compared metachronous inguinal hernia (MIH) incidence after both open and laparoscopic repair and reported that MIH occurred for 0.1% of patients that underwent laparoscopic repair where MIH occurred for 2.4% for those operated on through the classical open repair. [24] The authors concluded that CPPV repair in laparoscopy reduced the rate of subsequent of MIH however, 21 CPPV needed to be closed to prevent one MIH developing. [24] Another study also compared the incidence of MIH following open and laparoscopic hernia repair reported that following open repair, the incidence was 11.9%, whereas 0% of patient operated on laparoscopically developed MIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] A study compared metachronous inguinal hernia (MIH) incidence after both open and laparoscopic repair and reported that MIH occurred for 0.1% of patients that underwent laparoscopic repair where MIH occurred for 2.4% for those operated on through the classical open repair. [24] The authors concluded that CPPV repair in laparoscopy reduced the rate of subsequent of MIH however, 21 CPPV needed to be closed to prevent one MIH developing. [24] Another study also compared the incidence of MIH following open and laparoscopic hernia repair reported that following open repair, the incidence was 11.9%, whereas 0% of patient operated on laparoscopically developed MIH.…”
Section: Discussionmentioning
confidence: 99%
“…[24] The authors concluded that CPPV repair in laparoscopy reduced the rate of subsequent of MIH however, 21 CPPV needed to be closed to prevent one MIH developing. [24] Another study also compared the incidence of MIH following open and laparoscopic hernia repair reported that following open repair, the incidence was 11.9%, whereas 0% of patient operated on laparoscopically developed MIH. [25] Moreover, in a large series of more than 1000 patients, all of which were operated on laparoscopically, a very small MIH rate of 0.22% was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic hernia repair (LHR) can confirm the presence of contralateral patent processus vaginalis (CPPV). However, the incidence of CPPV evaluated by laparoscopy is 20–51.5%, which is much higher than the natural incidence of contralateral inguinal hernia (CIH) or MIH( 4 , 5 ). Ultrasonography is a safe and non-invasive method which helps to diagnose inguinal hernia and detect the presence of CPPV ( 6 8 ).…”
Section: Introductionmentioning
confidence: 93%
“…A total of 16 studies compared the incidence of metachronous hernia between the LHRE and OHR groups, and 15 of them with a total of 14,416 patients (5207 patients in the LHRE group and 9209 patients in the OHR group) with the diagnosis of unilateral inguinal hernia who received operation were assessed [21,[23][24][25][26][27]29,32,33,36,37,[40][41][42][43]. The pooled result indicated that LHRE resulted in a considerably lower incidence of metachronous hernia compared with OHR (RR: 0.11, 95% CI: 0.07 to 0.17; p < 0.00001; I 2 = 4%; Figure 2).…”
Section: Metachronous Herniamentioning
confidence: 99%
“…A total of 26 studies compared the incidence of ipsilateral recurrence hernia between the LHRE and OHR groups, and the data of 25 of them covered a total of 24,430 patients (12,626 patients in the LHRE group and 11,777 patients in the OHR group) were assessed [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][39][40][41][42][43]. The incidence of ipsilateral recurrence hernia did not differ between the LHRE and OHR groups (RR: 0.97, 95% CI: 0.59 to 1.60; p = 0.91; I 2 = 44%; Figure 3).…”
Section: Ipsilateral Recurrence Herniamentioning
confidence: 99%